Identiteit en seksualiteit in die Nuwe Testament - Steyn, Gert J. (Verbum et ecclesia, 2006)
This contribution wants to provide a broad overview of sexuality in the New Testament. It provides broad thematic stripes, picturing the early Christians as sexual beings with a new identity in Christ. Sexuality is a given in the New Testament, but due to their new identity, Christians’ sexuality displays particular features: it expresses its freedom responsibly; is driven by divine love; surrenders sacrificially to the other as Christ did; treats its partner as an equal and not as an object of self satisfaction; distinguishes itself from different cultural practices with an identity of its own; acknowledges the fact that it is part of an incomplete world; respects the identity of the other and despises all kinds of sexual malpractices; believes in forgiveness; and finds its climax ultimately and always in the presence of God.